Effect of Particle Size on Physicochemical Properties and in vitro Hypoglycemic Ability of Insoluble Dietary Fiber From Corn Bran - Jiang, Caixia; Wang, Rui; Liu, Xiaolan; Wang, Juntong; Zheng, Xiqun; Zuo, Feng (Frontiers in Nutrition, 2022)
This study was designed for determining the effect of particle size on the functional properties of corn bran insoluble dietary fiber (IDF). Results showed that some physicochemical properties were improved with the decrease in particle size. The structure of the IDF was observed by the scanning electron microscope (SEM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FT-IR). The surface was found wrinkled and sparse, the particle size was smaller, the crystallinity of IDF had increased slightly, and more -OH and C-O groups were exposed. Moreover, the corn bran IDF with a smaller particle size had a better hypoglycemic effect in vitro, and the inhibitory activity of α-glucosidase and α-amylase were also increased significantly with the decrease in particle size (p < 0.05). When the IDF was 300 mesh, the inhibitory rate of α-glucosidase was 61.34 ± 1.12%, and the inhibitory rate of α-amylase was 17.58 ± 0.33%. It had increased by 25.54 and 106.83%, respectively compared to the control treatment (CK) group. In addition, correlation analysis found that the particle size was highly negatively correlated with some functional properties of IDF (p < 0.05), and the content of cellulose was positively correlated with the functional properties of IDF except WHC (p < 0.05). To sum up, reducing particle size was suitable for the development of high value-added IDF products. This study also revealed the potential value of corn bran IDF and provided a new idea for the diversified application of IDF.